Microstructure analysis method for evaluating degenerated intervertebral disc tissue. (January 2017) - Friedmann, Andrea; Goehre, Felix; Ludtka, Christopher; Mendel, Thomas; Meisel, Hans-Joerg; Heilmann, Andreas; Schwan, Stefan
Highlights: IVD tissue was characterized using histology, light microscopy, and scanning electron microscopy to evaluate degeneration. Positive correlations seen between female gender and IVD cell density, age and cell size, and female gender and ECM thickness. No significant age/gender correlation to matrix delamination seen. Older patients were more often affected by the qualitative parameters evaluated. Abstract: Degeneration of intervertebral disc (IVD) tissue is characterized by several structural changes that result in variations in disc physiology and loss of biomechanical function. The complex process of degeneration exhibits highly intercorrelated biomechanical, biochemical, and cellular interactions. There is currently some understanding of the cellular changes in degenerated intervertebral disc tissue, but microstructural changes and deterioration of the tissue matrix has previously been rarely explored. In this work, sequestered IVD tissue was successfully characterized using histology, light microscopy, and scanning electron microscopy (SEM) to quantitatively evaluate parameters of interest for intervertebral disc degeneration (IDD) such as delamination of the collagenous matrix, cell density, cell size, and extra cellular matrix (ECM) thickness. Additional qualitative parameters investigated included matrix fibration and irregularity, neovascularization of the IVD, granular inclusions in the matrix, and cell cluster formation. The results of this study corroborated several previously published findings, including those positively correlating female gender and IVD cell density, age and cell size, and female gender and ECM thickness. Additionally, an array of quantitative and qualitative investigations of IVD degeneration could be successfully evaluated using the given methodology, resin-embedded SEM in particular. SEM is especially practical for studying micromorphological changes in tissue, as other microscopy methods can cause artificial tissue damage due to the preparation method. Investigation of the microstructural changes occurring in degenerated tissue provides a greater understanding of the complex process of disc degeneration as a whole. Developing a more complete picture of the degenerative changes taking place in the intervertebral disc is crucial for the advancement and application of regenerative therapies based on the pathology of intervertebral disc degeneration.